The Two Sides of Indoleamine 2,3-Dioxygenase 2 (IDO2) - Chiara Suvieri; Maria Laura Belladonna; Claudia Volpi (Cells, 2024)
Indoleamine 2,3-dioxygenase 1 (IDO1) and IDO2 originated from gene duplication before vertebrate divergence. While IDO1 has a well-defined role in immune regulation, the biological role of IDO2 remains unclear. Discovered in 2007, IDO2 is located near the IDO1 gene. Because of their high sequence similarity, IDO2 was initially thought to be a tryptophan (Trp)-degrading enzyme like IDO1. Differently from what expected, IDO2 displays extremely low catalytic activity toward Trp. Nevertheless, many studies, often contradictory, have tried to demonstrate that IDO2 modulates immune responses by catabolizing Trp into kynurenine, an unconvincing hypothesis linked to an incomplete understanding of IDO2’s activity. In this study, we review IDO2’s functional role beyond Trp metabolism. IDO2’s evolutionary persistence across species, despite being almost inactive as an enzyme, suggests it has some relevant biological importance. IDO2 expression in human normal cells is poor, but significant in various cancers, with two prevalent SNPs. Overall, the comparison of IDO2 to IDO1 as a Trp-degrading enzyme may have led to misunderstandings about IDO2’s true physiological and pathological roles. New insights suggest that IDO2 might function more as a signaling molecule, particularly in cancer contexts, and further studies could reveal its potential as a target for cancer therapy.